(Re)produksi Piil Pesenggiri: Identitas Etnis Lampung dalam Hubungan dengan Pendatang - Risma Margaretha Sinaga (Antropologi Indonesia, 2012)
This research is based on the mindset that any of heterogeneous in a society, they still could be identified based on the values or symbols that referred to them as an ethnic groups. The problem in this research comes from seeing the issues of Lampung ethnic as an experienced local ethnic domination that increasingly being desperate in their own cultural environment. Ambiguity and vagueness of identity as a local ethnic also reinforced by the attitude of immigrants towards them that affect the relationship between them and if it still left unchecked can potentially lead to conflict. This ethnography research aims to reveal how Lampung ethnic establish their existence of identity through cultural values of Piil Pesenggiri, which upholds the dignity contextually as Lampung identity which carried out in their actions as a strategy of contestation in the immigrant communities. The emergence of a awareness of their identity, reviving Piil Pesenggiri uphold the values of honour in local wisdom become a strategy and a capital that being used when they are dialing with immigrants. In their actualization, the reproduction of Piil Pesenggri still being based on its own basic values such as Pesenggiri, nemui nyimah, nengah nyappor, juluk adok, dan sakai sambayan. Contextually, Piil Pesenggiri become a strategy to manifested their existence as Lampung ethnic and it also used to change the stereotype that immigrants pinned to them with a new value such as (a) changing the work ethic that has been known so low that they are often associated with lazy, less ductile, weak competitiveness, and human resources are still limited; (b) are not stuck with the romance of the past as a landlord; (c) re-interpretation of the titles of nobility (juluk buadek) which has been become the pride and purpose to be achieved in the internal structure so that could be received in the external structure; (d) Piil Pesenggiri become an ethnic identity and politics identity. Piil Pesenggiri is a way of life how ethnic Lampung have to act and behave. For them, Piil Pesenggiri is an identity or reflects the identity so that their existence is recognized and valued in relation to immigrants. In order to confirm their identity as Lampung ethnics, then the actions and strategies they are doing is building a network through the structure of society, also using the idiom of kinship as a strategy to deal with the migrants so that their existence as an ethnic Lampung still got appreciation in accordance with the values of honour that contained in Piil Pesenggiri. Key words: Piil Pesenggiri, Reproduction, Identity